Is insufficient supervisory board competence a risk factor for banks? - Harald Hau; Tim-Ole Radach; Marcel Thum (CESifo GmbH, 2024)
The downfall of Credit Suisse should serve as a lesson that supervisory board competence determines the long-term risk of a bank. In a much-cited study, we investigated the relationship between competent board supervision and the performance of German banks during the 2008/2009 financial crisis. This policy brief summarizes the results of our updated study, which shows that despite legislative efforts, there is still a long way to go.
Keywords: 330